Prevalence of Stroke and Vascular Risk Factors in China: a Nationwide Community-based Study - Qi Li (Nature Portfolio, 2017)
Abstract We aimed to investigate the prevalence of stroke and related vascular risk factors in adult population aged 40 years and older in China. We conducted a prospective cross-sectional survey in nationally representative sample of 207323 individuals from all 31 Chinese provinces in 2013. Data were used to analyze the prevalence of stroke by age, sex, geographical regions and educational level. The age-standardized prevalence of stroke was significantly higher in men than in women in all age groups (P < 0.001). The age-standardized prevalence of stroke was significantly higher in rural than in urban residents among both men and women (P < 0.001). The prevalence of stroke was inversely associated with educational level. There were striking geographical variations in stroke prevalence in China with a higher prevalence of stroke in northern provinces as compared with southern provinces of the country. The age-standardized prevalence of hypertension, diabetes, dyslipidemia, atrial fibrillation and obesity in the Chinese population aged 40 years and older were 35.24%, 9.55%, 58.72%, 1.57% and 4.09%, respectively. Stroke and related vascular risk factors remains a major public threat in China and effective primary preventive strategies that aimed at reducing the burden of stroke and its risk factors are urgently needed.